Gariwerdichnus warreni igen. et isp. nov. — probable giant myriapod burrows from Late Silurian fluvial channels in the Grampians Group, Western Victoria, Australia. Issue 2 (3rd April 2021) - Gouramanis, Chris; Martin, Anthony J.; Webb, John A.
Abstract: Large Late Silurian burrows are preserved in fluviatile trough cross-bedded sandstones at Mount Bepcha and Mount William in the Grampians in western Victoria (Australia). These burrows have ventral surfaces with two parallel grooves likely formed by the trace-makers' paired legs as they burrowed through dunes on braided-river beds, probably after avulsion of sandy channels. The burrows are morphologically distinct from previously described burrows and a new ichnogenus Gariwerdichnus igen. nov. containing a single new ichnospecies G. warreni isp. nov. is erected. The size of the burrows, together with their ridged ventral surface, rounded dorsal surface with large dorsolateral protuberances, and meniscate backfill, point towards giant myriapods as the tracemakers. This conclusion is further supported by the presence of large Diplichnites isp. (including D. gouldi ) trackways of comparable size in a stratigraphically higher unit at Mount Bepcha; large D. gouldi are typically attributed to giant myriapods. Early myriapod groups that could have formed G. warreni include eoarthropleurids, arthropleurids, or a Bennettarthra- like organism. Chris Gouramanis [ chris.gouramanis@anu.edu.au ], Research School of Earth Sciences, The Australian National University, Australian Capital Territory, 0200, Australia; Anthony, J. Martin [ geoam@emory.edu ], Department of Environmental Sciences, Emory University, Atlanta, Georgia, 30322, USA; John A. Webb [ john.webb@latrobe.edu.au ], Department of Ecology, Environment and Evolution, La Trobe University, Bundoora, Victoria, 3086, Australia.